Participating—or Being Part of an Organizational Change: Narratives of Participation Related to School Closures to Reduce School Segregation - Flensner, Karin K.; Svensson, Ylva (International Journal of Education Policy and Leadership, 2024)
The mission of all primary schools includes offering all pupils educational quality and equality. Municipalities struggle with the negative consequences of school segregation, and some local councils decide to implement extensive changes in their school organization to offer all pupils equal opportunities. This study analyzes the experiences of staff and students when a local council implemented organizational changes to reduce the negative consequences of school segregation. A narrative analysis of documentation from the education authority and interviews with pupils and school staff were used to understand the perspectives of staff and pupils. There was strong support from the staff for implementing the changes but also strong criticism of how these changes were carried out. One conclusion is that municipalities implementing similar changes need to plan for the whole process and the participation of pupils and school staff in a systematic way.